Functional ANOVA investigation of the effects of friction welding parameters on the joint characteristics of aluminum based MMC to AISI 304 stainless steel - Balalan, Zulkuf; Ozdemir, Niyazi; Firat, Emrah Hanifi; Caligulu, Ugur (Carl Hanser Verlag, 2015)
This study investigates the applicability of joining an aluminum matrix composite, reinforced with 5, 10, and 15 wt.-% of SiCp particles, to AISI 304 austenitic stainless steel by using friction welding technique. In this study, optical and electron microscopes, lap shear strength test, and microhardness measurements were used to assess the quality of bonding of Al-Cu-SiCp and AISI 304 austenitic stainless steel joints performed by using friction welding. The strength of the friction welded joints was significantly affected by process parameters (rotation speed, friction time, friction pressure, forging time and forging pressure). Additionally, lap shear and axial shortening test results were analyzed by using analysis of variance (ANOVA) with a confidence level of 95 % to find out presence of a statistically significant difference.
Keywords: Friction welding; aluminum MMCs; austenitic stainless steel; ANOVA